1980
DOI: 10.1016/s0022-5347(17)55636-0
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Spermatocytic Seminoma

Abstract: Spermatocytic seminoma is noted generally for its relative infrequency of regional or distant metastases. A case of metastatic spermatocytic seminoma is reported in which there was radiographic evidence of tumor recurrence within an irradiated area. The need for aggressive initial management and careful followup of patients with this entity is emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…In 1980, Schoborg et al 25 reported an additional case of SS associated with metastases and fatal outcome 2 years after the initial presentation. The patient apparently died from the side effects of chemotherapy.…”
Section: Metastases In Spermatocytic Seminomamentioning
confidence: 99%
“…In 1980, Schoborg et al 25 reported an additional case of SS associated with metastases and fatal outcome 2 years after the initial presentation. The patient apparently died from the side effects of chemotherapy.…”
Section: Metastases In Spermatocytic Seminomamentioning
confidence: 99%
“…To further expand those recommendations, we set-up a multicenter registry and invite other centers to contribute their experiences in patients with spermatocytic tumors. Bohm et al (1993) After adjuvant and tumor negative modified template RPLND, retroperitoneal recurrence treated with neoadjuvant chemotherapy (BEP + PVB) followed by cytoreductive RPLND N/A Matoška et al (1988) RPLND + radiotherapy (38.4Gray) to the retroperitoneum, followed by PVB Died 25 months after orchiectomy during chemotherapy because of sepsis Mikuz et al (2014) BEP PEI + RPLND PD after 2 months PD, alive with metastases in liver and kidney Steiner et al (2006) Orchiectomy + 2 cycles adjuvant Carboplatin RPLND + 2xBEP PD after 10 months NED after 3 years follow-up Choi et al (2017) Radiotherapy to brain metastases PD Schoborg et al (1980) Radiotherapy to para-aortic and inguinal LNDs (2600 rad)…”
Section: Discussionmentioning
confidence: 99%
“…Schoborg [19] beschrieb 1980 einen Patienten, welcher bei Erstdiagnose in der Lymphographie vergrößerte paraaortale Lymphknoten aufwies und 6 Monate später axilläre Lymphknotenmetastasen entwickelte. Bei letzteren erfolgte eine histologische Diagnosesicherung mittels Nadelaspiratonsbiopsie.…”
Section: Krankheitsverlauf Und Therapieunclassified